Worsening trends in self-rated health and correlates in Chinese adolescents in Hong Kong: a population-based panel study from 1999/2000 to 2014/15. Issue 2 (14th February 2022) - Gong, Wei Jie; Fong, Daniel Yee Tak; Wang, Man Ping; Lam, Tai Hing; Chung, Thomas Wai Hung; Ho, Sai Yin
Abstract : Objectives: To examine the 15-year secular trends of self-rated health (SRH) and correlates in Chinese adolescents in Hong Kong. Design: A territory-wide population-based panel data study. Setting: Anonymised records of the annual health examination from the Student Health Service, Department of Health in Hong Kong. Participants: 397 324 students in Secondary 2 (US grade 8), 335 902 in Secondary 4 and 113 892 in Secondary 6 during the academic year 1999/2000 and 2014/15. Outcome measures: SRH and lifestyles were self-reported using standardised questionnaires. Sex-standardised and age-standardised prevalence of very poor/poor SRH and its secular annual changes across sex, grade, weight status, breakfast habits, and frequency/duration of aerobic exercises were examined. Their disparities over time were examined by interactions with the academic year in generalised estimating equations. Results: The overall prevalence of very poor/poor SRH increased from 9.3% (95% CI: 8.9% to 9.7%) in 1999/2000 to 15.5% (15.1% to 15.8%) in 2014/15. Very poor/poor SRH was more prevalent in girls (adjusted OR: 1.02), in those having unemployed parents (1.29), being overweight (1.42) or obese (2.62), eating breakfast away from home (1.27) and skipping breakfast (1.49) or doing <1 time/week or ≤60 min/week aerobic exercises (1.78 and 1.88, respectively) than others. The corresponding disparities increased over time (ratios of OR: 1.006–1.042). Conclusions: Increasing prevalence of very poor/poor SRH from 1999/2000 to 2014/15 was found among Hong Kong Chinese adolescents, which was greater in girls, adolescents being overweight/obese and those having unemployed parents or unhealthy lifestyles. Strategies to reduce health inequality should consider multiple factors, especially modifiable factors including lifestyles.